Reliability of information systems in organizations as a factor shaping organizational culture - Tworek, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
This paper analyses the potential relation between IS reliability and organizational culture. Based on the literature review, the research gap is identified and hypotheses concerning the potential role of IS in shaping organizational culture are proposed. The community-oriented culture is suggested as a potential direction of culture reorganization. The hypotheses are verified based on the empirical research performed in 2017 in 400 organizations in Poland. The research results indeed confirmed that IS can be considered as one of the factors shaping organizational culture. However, the direction of its change appeared to be different than the one presented in the current literature
Argumenta Oeconomica, 2020, Nr 2 (45), s. 259-274
Keywords: information systems; IS reliability; organizational culture